A CASE STUDY ON SCHIZOPHRENIA INDUCED MULTIPLE COMORBIDITIES - M, Jagadeesan; Kumar R, Kiran; Abraham, Justin Jacob (Asian Journal of Pharmaceutical and Clinical Research, 2018)
Schizophrenia is a mental disorder characterized by abnormal social behavior which includes false beliefs, confusion, and auditory hallucination. Antipsychotic drugs therapy increases the risk of developing diabetes mellitus and coronary artery disease (CAD) in schizophrenic patients. Hence, we have planned for a systematic approach toward the management of comorbidities induced in schizophrenic patients. A case study was conducted in 42-year-old female patient diagnosed with schizophrenia along with Type-2 diabetes mellitus, hypothyroidism, diabetic retinopathy, diabetic nephropathy, systemic hypertension, CAD-acute coronary syndrome recent inferior wall myocardial infarction. The patient was treated with atypical antipsychotics, antiplatelets, antianginals, statins, hypoglycemic agents, and other supportive measures. The patient improved symptomatically. The antipsychotic treatment for schizophrenia induces abnormal metabolic syndrome which results in decreased glucose and lipid metabolism that leads to obesity, hyperglycemia, and dyslipidemia associated with cardiovascular risks. Often antipsychotics are combined with benzodiazepines and antiparkinson agents to reduce the risks caused from large doses of antipsychotic medication. However, people receiving first-generation antipsychotics have higher prevalence of developing diabetes mellitus and cardiac risks compared to second-generation antipsychotics. Hence, we conclude that atypical antipsychotic drugs such as amisulpride, aripiprazole, and ziprasidone should be given to schizophrenic patients because these drugs have little effects on abnormal metabolic syndrome when compared to other antipsychotics. There is a need for proper screening of blood glucose level and cardiovascular risks assessment before the administration of antipsychotic medications to schizophrenic patients and also during the course of treatment regularly.